Primary colors : a novel of politics (New York : Random House, 1996)
The electoral campaign of a Southern governor for the presidency of the United States. Narrated by a half-black campaign staffer, the novel follows the governor--ably assisted by his dynamic wife, a lawyer--as he mixes calculation with sincerity, dodges a draft-controversy bullet, gorges on barbecues, poaches off others' plates, seduces the occasional innocent bystander and confronts the resulting sex scandals.
Keywords: Presidents -- Election -- Fiction; Political campaigns -- Fiction; Political fiction; Political fiction